2022
DOI: 10.3389/fphar.2021.799130
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Derived Growth Factor-BB Inhibits Intervertebral Disc Degeneration via Suppressing Pyroptosis and Activating the MAPK Signaling Pathway

Abstract: Platelet-derived growth factor-BB (PDGF-BB) is a cytokine involved in tissue repair and tumor progression. It has been found to have expression differences between normal and degenerative intervertebral discs. However, it is not clear whether PDGF-BB has a protective effect on intervertebral disc degeneration (IDD). In this experiment, we treated nucleus pulposus cells (NPCs) with IL-1β to simulate an inflammatory environment and found that the extracellular matrix (ECM) anabolic function of NPCs in an inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…The most enriched biological process was Response to oxidative stress, cellular component was Cytoplasm, and molecular function was Identical protein binding. More importantly, we also investigated the potential signaling pathways involved in the repair process of NPCs cocultured with MSCs, and some of these signaling pathways have been proved to play important roles in the pathophysiology of IDD [38][39][40][41][42]. TNF signaling pathway and IL-17 signaling pathway both were inflammation-related pathways, which indicated that MSCs might reduce the oxidative stress, and then improve the inflammatory status of degenerative NPCs [38,39].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The most enriched biological process was Response to oxidative stress, cellular component was Cytoplasm, and molecular function was Identical protein binding. More importantly, we also investigated the potential signaling pathways involved in the repair process of NPCs cocultured with MSCs, and some of these signaling pathways have been proved to play important roles in the pathophysiology of IDD [38][39][40][41][42]. TNF signaling pathway and IL-17 signaling pathway both were inflammation-related pathways, which indicated that MSCs might reduce the oxidative stress, and then improve the inflammatory status of degenerative NPCs [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…TNF signaling pathway and IL-17 signaling pathway both were inflammation-related pathways, which indicated that MSCs might reduce the oxidative stress, and then improve the inflammatory status of degenerative NPCs [38,39]. MAPK signaling pathway was another vital biolog-ical pathway in the development of IDD [40][41][42] 7 Stem Cells International degenerative NPCs cocultured with MSCs. Both relaxin and oxytocin have been demonstrated to exert important protective effects in human diseases by inhibiting the cell apoptosis [43][44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, some growth factors are considered as a possible therapeutic to improve IVD tissue regeneration. Indeed, platelet-derived growth factor (PDGF), insulin-like growth factor 1 (IGF-1), growth differentiation factor 5 (GDF-5), bone morphogenetic protein 2 (BMP-2), and bone morphogenetic protein 7 (BMP-7) have been explored as viable treatment alternatives for IVD regeneration [ 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 ]. Furthermore, VEGF is highly expressed in the injured IVD, and mutational variations in the VEGF gene are associated with lumbar disc degeneration in a young Korean population [ 164 ].…”
Section: Genetics Of Ivddmentioning
confidence: 99%